Retorik bahasa Tamil dalam pengumuman pemasaran nilai sosial THR Raaga / Kalaiselvi Shanmugam - Shanmugam, Kalaiselvi (2012)

(untitled)
This research attempts to scrutinize the usage of rhetoric strategies in a program called PNS which is aired by a private radio channel called THR Raaga. This research aims to identify the rhetoric strategies that are aired in PNS as well as describe them systematically in qualitative and quantitative forms. Phrases that contain a certain rhetoric strategy will also be identified and portrayed. Besides this, the effectiveness of the PNS announcements will also be studied from the listeners’ view about this program. Library research was done as a base for this study. A research framework suggested by Cobert & Connors in 1999 is used to analyze the PNS announcements in THR Raaga. Forty episodes have been segmented sentence by sentence to be made as research samples. The researcher has used three instruments in this study. Data were obtained through systematic recording, questionnaires, and interviews. Fifty respondents have been chosen to answer the questionnaires that cover five categories of listeners. From these 50 respondents, one respondent from each category has been chosen to be interviewed. The research findings show that there are 88 scheme and 43 trope styles of rhetoric strategies in the PNS announcements. Epistrope rhetoric has been used widely; as many as 19 times (21.6%) compared to all other rhetoric styles. Rhetoric question from the trope style has also been widely used. This rhetoric has been used 17 times (39%) from the total rhetoric strategies.